2012
DOI: 10.1016/j.physa.2011.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo Hermitian formulation of the quantum Black–Scholes Hamiltonian

Abstract: We show that the non Hermitian Black-Scholes Hamiltonian and its various generalizations are η-pseudo Hermitian. The metric operator η is explicitly constructed for this class of Hamitonians.It is also shown that the effective Black-Scholes Hamiltonian and its partner form a pseudo supersymmetric system. * Electronic address: tapasisi@gmail.com †

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…With these definitions, in [12] was also shown that B = ρ −2 A † ρ 2 . Hence B = A † if ρ = 1 1, which is true only if β = 0, see (3.3).…”
Section: D-pbs From the Black-scholes Equationmentioning
confidence: 98%
See 4 more Smart Citations
“…With these definitions, in [12] was also shown that B = ρ −2 A † ρ 2 . Hence B = A † if ρ = 1 1, which is true only if β = 0, see (3.3).…”
Section: D-pbs From the Black-scholes Equationmentioning
confidence: 98%
“…In [10,11,12] some real potential V (x) is added to the operator H BS , defining in this way a new operator, H ef f = H BS + V (x). The economical interpretation of V (x), see [10], is that it can be used to represent a certain class of options; we will not insist on that here.…”
Section: D-pbs From the Black-scholes Equationmentioning
confidence: 99%
See 3 more Smart Citations